Selection of volleyball players using fuzzy electre / Fatin Afiqah Mohd Hanafiah - Mohd Hanafiah, Fatin Afiqah (Faculty of Computer and Mathematical Sciences, 2019)
Sport psychology is a right proficiency to setting a good organization and builds relationship between coach and team. The situation where coach must forming the good team that need to consider the human behaviour and their potential in volleyball game was difficult task. Coach need to really understand the abilities of their players based on what they see combined with what they feel on the performance. The question is how far their perception is true without any reason. The coach who has knowledge and long experience in one’s game that is not enough to make assumption towards on capabilities of players. To determine whether someone is good or not, as a coach must looking on many ways and dimension to come out with the reason to support their assumption. Fuzzy ELECTRE was evaluated 10 volleyball players. The aims of this study are to determine the most important criteria, to compare fuzzy ELECTRE with conventional method and to select the players based on the performance. Analysis was evaluated on 10 players by looking six important criteria need in the selection using fuzzy ELECTRE. The result gain was different when number of players’ rank is different between use fuzzy ELECTRE and conventional method. Therefore, fuzzy ELECTRE can help coach to more confidence for make decision in their selection